2018
DOI: 10.3389/fnins.2018.00582
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitive Effects of FGF2/FGFR1 Pathway on Astrocyte-Mediated Inflammation in vivo and in vitro After Infrasound Exposure

Abstract: Infrasound, a kind of ambient noise, can cause severe disorders to various human organs, specially to central nervous system (CNS). Our previous studies have shown that infrasound-induced CNS injury was closely related with astrocytes activation and astrocytes-mediated neuroinflammation, but the underlying molecular mechanisms are still largely unclear. FGF2/FGFR1 (Fibroblast growth factor 2/Fibroblast growth factor receptor 1) pathway was reported to play an important role in anti-inflammation in CNS disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 58 publications
(70 reference statements)
2
18
0
Order By: Relevance
“… 523 However, FGF2/FGFR1 pathway has inhibitive effects on astrocyte-mediated neuroinflammation after infrasound exposure. 524 In turn, there is a profound reduction in FGFR1 in human umbilical vein ECs treated by TNF-α and IL-1β, while other inflammatory cytokines such as IL-6 could not inhibit the expression of FGFR1. 476 Besides, our group recently identified that FGFR3 deficiency promoted chemotaxis of macrophages via activation of NF-κB/CXCR7 signaling pathway, which reveals the negative role of FGFR3 in synovial inflammatory response.…”
Section: Fgf Signaling In Inflammatory Responsementioning
confidence: 93%
“… 523 However, FGF2/FGFR1 pathway has inhibitive effects on astrocyte-mediated neuroinflammation after infrasound exposure. 524 In turn, there is a profound reduction in FGFR1 in human umbilical vein ECs treated by TNF-α and IL-1β, while other inflammatory cytokines such as IL-6 could not inhibit the expression of FGFR1. 476 Besides, our group recently identified that FGFR3 deficiency promoted chemotaxis of macrophages via activation of NF-κB/CXCR7 signaling pathway, which reveals the negative role of FGFR3 in synovial inflammatory response.…”
Section: Fgf Signaling In Inflammatory Responsementioning
confidence: 93%
“…Furthermore, human and animal experiments have suggested that prolonged infrasound exposure can damage the central nervous system (CNS), including the hippocampus, cerebellum, limbic-corticular complex, hypothalamus, and cortex (Izmerov et al, 1997; Fei et al, 2000; Yuan et al, 2009; Shi et al, 2013; Cai et al, 2014; Ma et al, 2015). We previously confirmed that infrasound exposure activated astrocytes and induced neuronal apoptosis in the CNS, which subsequently impaired spatial learning and memory abilities (Shi et al, 2013, 2018).…”
Section: Introductionmentioning
confidence: 56%
“…The rats were divided randomly into groups as described previously (Shi et al, 2018): control group (no infrasound exposure, n = 6), infrasound (IS) exposure groups (exposed to 16 Hz, 150 dB of infrasound for 1, 3, 5, or 7 days, n = 6 per group), FGF2 groups (treated with FGF2 for 1, 3, 5, or 7 days, n = 6 per group), PD groups (treated with PD173074 for 1, 3, 5, or 7 days, n = 6 per group), FGF2+IS groups (infrasound-exposed rats treated with FGF2, n = 6 per group), and PD + IS groups (infrasound-exposed rats treated with PD173074, n = 6 per group). For FGF2 administration, rats were injected intraperitoneally (i.p.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of the FGF2/FGFR1 pathway aggravated astrocyte-mediated inflammation after infrasonic exposure. The authors concluded that astrocyte-mediated inflammation was involved in infrasound-induced neuronal damage and that the FGF2/FGFR1 pathway played a key role [56].…”
Section: The Hippocampusmentioning
confidence: 99%